2020
DOI: 10.3390/pr8101251
|View full text |Cite
|
Sign up to set email alerts
|

Study on Two Types of Stall Patterns in a Centrifugal Compressor with a Wide Vaneless Diffuser

Abstract: Two types of stall patterns in the centrifugal compressor with a wide vaneless diffuser were numerically studied in this paper. We carried out kinds of three-dimensional numerical simulations of the instability process in wide vaneless diffusers with different radius ratios. The results show that there are two kinds of stall patterns in wide vaneless diffusers with different radius ratios. For a short diffuser with a radius ratio of 1.5, the speed of the propagation of stalled cells is relatively high, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ibaraki [9,10] found that the interaction of shock wave and tip leakage flow enhanced the blockage of the blade channel and caused flow loss in a transonic centrifugal compressor. Owing to the complex flow behavior mentioned above, the efficiency [11] and Stable Flow Range (SFR) [12,13] declined sharply with increasing pressure ratio in a centrifugal compressor. Therefore, the low efficiency and narrow SFR severely restrict the development and application of high-pressure-ratio centrifugal compressors, and this situation could become more severe with the design pressure ratio increased to an ultra-high level (higher than 10.0).…”
Section: Introductionmentioning
confidence: 99%
“…Ibaraki [9,10] found that the interaction of shock wave and tip leakage flow enhanced the blockage of the blade channel and caused flow loss in a transonic centrifugal compressor. Owing to the complex flow behavior mentioned above, the efficiency [11] and Stable Flow Range (SFR) [12,13] declined sharply with increasing pressure ratio in a centrifugal compressor. Therefore, the low efficiency and narrow SFR severely restrict the development and application of high-pressure-ratio centrifugal compressors, and this situation could become more severe with the design pressure ratio increased to an ultra-high level (higher than 10.0).…”
Section: Introductionmentioning
confidence: 99%
“…Centrifugal compressor has the advantages of compact structure, durability, and highpressure ratio, and there is a lot of research on targeted applications in the corresponding fields [1][2]. In the past, the research on centrifugal compressors mainly focused on aerodynamic aspects, and the main goal of this research work was to improve efficiency, pressure ratio and operating range [3].…”
Section: Introductionmentioning
confidence: 99%